Accessibility of Gynecological Healthcare Services in Canada Under Immigration Policies - Kristina Telman; Santiago Sammie; Birgit Kamal (Studies in Social Science & Humanities, 2023)
This study examines the accessibility of gynecological healthcare services for immigrant women in Canada and explores the impact of immigration policies on their healthcare access. With a diverse immigrant population, Canada’s healthcare system faces the challenge of addressing disparities in healthcare utilization among newcomers. We investigate the barriers faced by immigrant women in accessing gynecological care, including language barriers, cultural and stigma-related challenges, and economic factors. We analyze government initiatives and community programs aimed at improving healthcare access for immigrant women. The study concludes with policy recommendations and strategies to promote awareness, emphasizing the importance of a comprehensive approach to ensure equitable healthcare access for all immigrants in Canada.